Lipoma Arborescens: Review of an Uncommon Cause for Swelling of the Knee - M. De Vleeschhouwer; E. Van Den Steen; G. Vanderstraeten; W. Huysse; J. De Neve; L. Vanden Bossche (Case Reports in Orthopedics)
Lipoma arborescens is a rare cause of chronic monoarticular arthritis, with only a few cases reported in the literature. It is most commonly seen in the knee, but cases in other joints such as the wrist, shoulder, and elbow have also been described. It is a benign condition, in which the subsynovial tissue is replaced diffusely by mature fat cells. We describe a case involving the knee and discuss the symptoms, diagnosis, and treatment.